1978
DOI: 10.1093/oxfordjournals.aje.a112608
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity as an Index of Heart Attack Risk in College Alumni1

Abstract: Risk of first heart attack was found to be related inversely to energy expenditure reported by 16,936 Harvard male alumni, aged 35-74 years, of whom 572 experienced heart attacks in 117,680 person-years of followup. Stairs climbed, blocks walked, strenuous sports played, and a composite physical activity index all opposed risk. Men with index below 2000 kilocalories per week were at 64% higher risk than classmates with higher index. Adult exercise was independent of other influences on heart attack risk, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
348
1
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,688 publications
(352 citation statements)
references
References 0 publications
1
348
1
2
Order By: Relevance
“…In a study of 470 163 Taiwanese adults, Li et al reported that, among hypertensive individuals, risk of mortality was 37% higher for those who were inactive compared with those who were active 6. Among participants in the Harvard Alumni Health Study, Paffenbarger et al found that men with a high level of physical activity (≥2000 kcal/wk) had lower rates of heart attack than those with a low level of physical activity (<2000 kcal/wk), even in the presence of various cardiovascular risk factors, including older age, smoking, and obesity 9. In a follow‐up to this analysis, Sesso and colleagues found that, among men with multiple (≥4) CVD risk factors, those who were more active had reduced CHD risk compared with those who were less active 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 470 163 Taiwanese adults, Li et al reported that, among hypertensive individuals, risk of mortality was 37% higher for those who were inactive compared with those who were active 6. Among participants in the Harvard Alumni Health Study, Paffenbarger et al found that men with a high level of physical activity (≥2000 kcal/wk) had lower rates of heart attack than those with a low level of physical activity (<2000 kcal/wk), even in the presence of various cardiovascular risk factors, including older age, smoking, and obesity 9. In a follow‐up to this analysis, Sesso and colleagues found that, among men with multiple (≥4) CVD risk factors, those who were more active had reduced CHD risk compared with those who were less active 10.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this inverse association has been shown in various high‐risk subgroups, including older adults, current smokers, and adults with diabetes mellitus (DM), hypercholesterolemia, or hypertension 2, 3, 5, 6, 7, 8, 9, 10. Although physical activity reduces CVD risk in people with and without single CVD risk factors, it is unclear if physical activity is equally beneficial for prevention of CVD among women with varying levels of global cardiovascular risk.…”
mentioning
confidence: 99%
“…It is well documented that increased age [7, 8], poor functional work capacity [9], chronotropic incompetence [10], extent of myocardial ischemia [11, 12], extent and history of previous myocardial infarction [13, 14], low ejection fraction [15, 16, 17], and increased end diastolic volume [15, 16, 17]are all independent predictors of increased cardiac mortality.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Even if current PA level is known to have the greatest effect on health and physical performance in general, 3,4 childhood and adolescence PA might also have important beneficial effects in different domains, for example, bone density. 5 With the alarming reports of increasing childhood/adolescent obesity and declining fitness levels, 6,7 studies on the immediate effects on health and disease in youth, as well as tracking into adulthood and effects on lifestyle, activity habits, and health later in life, are highly relevant.…”
mentioning
confidence: 99%